SCAT2 and SCAT3 scores at baseline and after sports-related mild brain injury/concussion: qualitative synthesis with weighted means. Issue 1 (19th October 2016) - Thomas, Roger E; Alves, Jorge; Vaska, Marcus M; Magalhães, Rosana
Abstract : Objective: Identify all Sport Concussion Assessment Tool (SCAT2/3) studies, compare baseline and postconcussion results. Design: Systematic review (qualitative synthesis, weighted means). Data sources: 18 databases, 9 grey literature resources searched for SCAT2/3 data; 9150 articles identified, titles/abstracts assessed/data-entry independently by two reviewers. Eligibility criteria for selecting studies: Any studies reporting partial/complete SCAT2/3 data. Results: 21 studies with data (partial/complete data 16 SCAT2 (4087 athletes); 5 SCAT3 (891). Newcastle-Ottawa risk-of-bias scale: studies with maximum possible score of 4, 85% scored 3 or 4; studies with maximum possible score of 6, 75% scored 5 or 6. SCAT2 high schoolers: weighted mean score for symptoms 18.46 (22=no symptoms), Balance Error Scoring System (BESS) 26.14, Standardised Assessment of Concussion (SAC) 26.00 and SCAT2 total 88.63. Collegiate/adults weighted means: symptoms 20.09, BESS 25.54, SAC 27.51 and total SCAT2 91.20. Between-study and within-study variability similar to those of the high schoolers. Limited variability between genders. Only 2 studies report baseline and postconcussion scores and 9 partial scores, but data are too limited to provide weighted average scores. Conclusions: Group mean baseline SCAT scores for high school and collegiate athletes are similar, with minimal gender differences; baseline symptoms show more variability than other components. There are minimal data for elementary students and professionals, no data for adult non-collegiate athletes. Two studies provide preconcussion and postconcussion scores. No data on minimal significant clinical differences to guide players/coaches in withdrawing from a game in progress and deciding when recovery is complete and play can be resumed. The SCAT needs supplementing with clinical and neuropsychological return-to-play assessments.